Preterm birth subtypes, placental pathology findings, and risk of neurodevelopmental disabilities during childhood. (August 2019) - Raghavan, Ramkripa; Helfrich, Blandine Bustamante; Cerda, Sandra R.; Ji, Yuelong; Burd, Irina; Wang, Guoying; Hong, Xiumei; Fu, Lingling; Pearson, Colleen; Daniele Fallin, M.; Zuckerman, Barry; Wang, Xiaobin
Abstract: Introduction: Preterm birth (PTB) and in-utero inflammation are recognized risk factors of neurodevelopmental disabilities (NDDs); however, their combined role in NDDs is unknown. We examined the independent and joint association of PTB and placental histological findings with the childhood risk of NDDs (overall and by subgroups including autism spectrum disorder (ASD) and ADHD). Methods: We analyzed data from the Boston Birth Cohort, where mother-infant pairs were enrolled at birth and followed from birth onwards. Birth outcomes, placental pathology and NDDs were obtained from electronic medical records. Placental pathology was categorized using a standardized classification system proposed by the Amsterdam Placental Workshop Group. Results: PTB (all, including spontaneous, medically indicated) was an independent risk factor for NDDs. Placental histological chorioamnionitis (CA) and PTB additively increased the odds of NDDs (aOR: 2.16, 95% CI: 1.37, 3.39), as well as ADHD (aOR: 2.75, 95% CI: 1.55, 4.90), other developmental disabilities (aOR: 1.96, 95% CI: 1.18, 3.25) and possibly ASD (aOR: 2.31, 95% CI: 0.99, 5.39). The above associations were more pronounced in spontaneous than medically indicated PTB. PTB alone in the absence of CA only had a moderate association with ASD and ADHD. Placental maternal vascular malperfusion alone or in combination with PTB was not associated with the risk of NDDs. Discussion: Our study provided new insights on PTB and NDDs by further considering preterm subtypes and placental histology. We revealed that children of spontaneous PTB along with histological CA were at the highest risk for a spectrum of NDDs. Highlights: PTB and histological chorioamnionitis (CA) additively increase the risk of NDDs. Spontaneous PTB with histological CA are associated with highest risk of NDDs. Maternal vascular malperfusion does not increase the risk of NDDs.